Respiratory Pathogens: A Comparison between Pre- and Post-pandemic Situation of COVID-19 - Kim , Ki Yeon; Kim , Jae Soo; Lee , Young Ki; Kim , Ga Yeon; Jung , Bo Kyeung (Current Innovations in Disease and Health Research Vol. 7, 2023)
This investigation aims to determine how respiratory pathogens changed both before and after the COVID-19 epidemic, a kind of viral pneumonia for which a pandemic was proclaimed (March 2020). Pneumonia is an infection that affects one or both lungs. It causes the air sacs, or alveoli, of the lungs to fill up with fluid or pus. Bacteria, viruses, or fungi may cause pneumonia. To determine the relationship between personal cleanliness and the prevention of infection by respiratory pathogens, the data were broken down by gender and age. A retrospective analysis was performed on 39,814 sputum, bronchial aspirate, and transtracheal aspirate samples obtained from 15,398 patients visiting a university hospital, located in Chungcheongnam-do, South Korea, between January 2018 and December 2021. From 4,454 patients whose samples were culture positive for bacteria, 6,389 strains were isolated and further cultured. The outpatients with respiratory pathogens had a mean age of 66.2 years, and when the results of the culture tests were compared by gender, it was found that males made up 64.9% (2,892/4,454) and females made up 35.1% (1,562 out of 4,454). The number of outpatients who requested respiratory microbial cultures following the start of the pandemic was decreased by 20.7% compared to the pre-COVID-19 pandemic period, and the number of outpatients who had a positive culture result was decreased by 23.0%. Following the pandemic, the number of respiratory samples obtained decreased by 6.7% while the sample positive rate decreased by 18.3%. When compared to pre-COVID-19 levels, the isolated microbial strains showed a significant reduction for the Acinetobacter baumannii complex (43.1%), Streptococcus pneumoniae (60.5%), Haemophilus influenzae (67.2%), and Moraxella catarrhalis (78.1%). According to the distribution of respiratory microbial strains by age group, patients above the age of 70 had the highest prevalence of isolated bacteria. The improvements in personal hygiene due to the COVID-19 pandemic exerted a substantial influence on the pattern of change in other common respiratory microorganisms, which highlights the importance of personal hygiene management in the prevention of respiratory infections.